ANALYSIS OF TEACHING FACTORY IMPLEMENTATION IN VOCATIONAL SCHOOL CASE STUDY: PUBLIC VOCATIONAL HIGH SCHOOL 1 LABUAN BAJO - Gregorius Antariksa Berybe; Maksimus Diamat; Yohanes Paulus Hanny Wadhi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Teaching Factory is a learning model at Vocational School based on production/services that refer to standards and procedures applied in the industry. The implementation of the Teaching Factory requires industry involvement. Parameters to measure the achievement of the Teaching Factory implementation are management, facilities, learning patterns, marketing-promotions, products-service, human resources, and industrial relations. The purpose of the research in this paper is to find out the implementation of the Teaching Factory in the Hospitality Program at Public Vocational High School 1 Labuan Bajo. The research uses the qualitative descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed by reducing, displaying, and verifying data. The results indicate that the achievement of the implementation of the Teaching Factory in the Hospitality Program at Public Vocational High School 1 Labuan Bajo, based on several achievement measurement parameters, there are still some shortcomings in terms of Management, Marketing-promotion, Human Resources, and learning patterns. The need for commitment to the implementation and evaluation of Teaching Factory must be applied to improve the quality of learning to produce graduates who are competent for industry needs.